Needs and preferences of women users of oral contraceptives in selected countries in Central and Eastern Europe - Tomas Fait; Dmitry Buryak; Monica-Mihaela Cirstoiu; Eva Luczai; Rafal Janczura (BioExcel Publishing Ltd, 2018)
Background: The availability of various oral contraceptive (OC) pill formulations with different hormone compositions suggests that there is potential to align a particular product with an individual user's needs and preferences. To explore this concept further, a survey was conducted of current users of OCs to define and confirm areas of specific needs, and to gain insight into their views and preferences for OC formulations. Methods: During November and December 2015, women users (n=615) of OCs in five Central and Eastern European countries were surveyed in face-to-face interviews conducted by experienced interviewers. The survey questionnaire comprised 34 questions about the use of and specific needs for OCs. Results: Four basic needs of women taking OCs were identified: reliable contraception, reversibility of contraception, no effect on body weight and safety. Overall, 85% of surveyed women indicated that prevention of pregnancy was the main reason for taking OCs. Weight gain was the side effect of greatest concern with OC use (46% spontaneous answer; 65% aided answer). Independent behavioural segmentation analysis identified four groups - Solved Cycle Problems (46% of participants), Low Hormone Content (22%), Lifestyle (17%) and Beauty (14%) - which characterised the women according to needs and preferences beyond the basic needs of OCs. Each group had unique features and distinct preferences for different formulations of OCs. Conclusions: Aligning product advantages with specific individual needs may enhance users' overall experience with OCs as a contraceptive option.